2006
DOI: 10.1007/s11082-006-0024-7
|View full text |Cite
|
Sign up to set email alerts
|

Effective Mode Volume of Nanoscale Plasmon Cavities

Abstract: Effective mode volume of nanoscale plasmon cavitiess t e f a n a . m a i e r Abstract. The controlled squeezing of electromagnetic energy into nanometric volumes via surface plasmon-polariton excitations in plasmonic nanoresonators is analyzed using the concept of an effective electromagnetic mode volume V eff , while taking careful account of the plasmon-polariton dispersion and the electromagnetic energy stored in the metal. Together with the quality factor Q of the cavity resonance, this enables a compariso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 32 publications
(24 reference statements)
1
51
0
Order By: Relevance
“…consistently with experimental observations. 16 In Fig. 4b, we show the scattering cross-section spectra of the bare nanorod (blue) and the perturbed nanorod (5-nm shell, red).…”
Section: Local Field Correctionsmentioning
confidence: 99%
“…consistently with experimental observations. 16 In Fig. 4b, we show the scattering cross-section spectra of the bare nanorod (blue) and the perturbed nanorod (5-nm shell, red).…”
Section: Local Field Correctionsmentioning
confidence: 99%
“…Some care must be taken in rigorous mode volume calculations in these systems [58], [59]. For a medium with negative dielectric constant, appropriate approximations must be used to avoid negative energy density terms.…”
Section: B Purcell Enhancement Of Spontaneous Emissionmentioning
confidence: 99%
“…In comparison between a nanoscale plasmon cavity and a dielectric optical one, it has been shown that the effective electromagnetic mode volume is not limited by diffraction in the former structures (Maier 2006).…”
Section: Introductionmentioning
confidence: 99%